Interleukin-1 beta (IL-1 beta) levels in gingival crevicular fluid from adults with previous evidence of destructive periodontitis. A cross sectional study - Wilton, J M; Bampton, J L; Griffiths, G S; Curtis, M A; Life, J S; Johnson, N W; Powell, J R; Harrap, G J; Critchley, P (Journal of clinical periodontology, 1992)
We have estimated the levels of Interleukin-1 beta (IL-1 beta) by ELISA in gingival crevicular fluid (GCF) at 58 sites from 37 patients with adult periodontitis. GCF was collected for 5 s on filter papers and a 2nd sample was collected for 30 s 1 min later. 68/116 strips yielded detectable levels of IL-1 beta. IL-1 beta was present in both the 1st and 2nd samples at 28 sites, in the 1st only at 4 sites and in the 2nd only at 8 sites; 18 sites were below the level of detection for the assay. When the concentrations of IL-1 beta were calculated in the original volume of GCF on each strip, the mean value for positive strips was 34.16 +/- 29.45 (SD) pg/microliters with a range from 1.75 to 97.13 pg/microliters. There were no statistically significant correlations with the plaque index, bleeding index or probable crevice depth (pocket depth). The results indicate that IL-1 is present in the GCF from a proportion of sites with evidence of previous periodontal destruction.